Long rallies and next rally performances in elite men`s and women`s badminton - Gomez, M. A.; Leicht, A. S.; Rivas, F.; Furley, P. (PLOS ONE, 2020)
The aim of the present study was twofold: (i) to identify contextual variables associated with the occurrence of long rallies while investigating time-related and technical parameters; and (ii) to identify performance differences between long rallies and the subsequent rally when accounting for match-context and the players` sex. The sample included 60 men`s (n = 4,475 rallies) and 60 women`s (n = 4,490 rallies) matches randomly selected from the 2015 World Badminton Super Series and World Championship (the final sample included long rallies that had an immediate next point played: n = 1,734 and n = 1,644 rallies for male and female players, respectively). The long rallies represented 19.4% (n = 867) and 16.5% (n = 822) of total rallies for male and female players, respectively. Long rallies were established using a two-step cluster model based on rally time and number of strokes for male (13-79s, 14-72 strokes) and female players (11-56s, 11-52 strokes). The variables collected were point outcome (when serving and receiving, winner, forced-error and unforced-error), number of strokes per rally, rally time, rest time, density, and time between strokes. The rallies were classified into different contexts (clusters) according to influencing factors with eight clusters for male players and three clusters for female players identified. Comparisons among clusters were conducted using Kruskal Wallis and one-way ANOVAs. Comparisons between long and immediate next points were conducted using the Wilcoxon tests for most variables and Crosstabs Command for point outcome and rallies (long and immediate next). Statistically significant differences were identified for both sexes among clusters only for time-related variables (i.e., rally time, rest time, density and time between strokes). In addition, a greater number of strokes, longer rally, rest time, and higher density were identified during long rallies compared with the immediate next rally for both men`s and women`s matches (p<0.05). The time between strokes during long rallies was significantly greater for male players during clusters 3, 5, 6, and 7 (p<0.05) and significantly lower for female players during all clusters (p<0.05). Significant relationships were identified between winning point outcome, and more unforced errors when serving during the immediate next rally (men`s cluster 5 and women`s cluster 2), and more winners when serving during the immediate next rally (men`s cluster 6). The current study identified and characterised long rallies in elite men´s and women´s badminton matches highlighting the importance of sex and contextual factors on time-related and technical demands. Information obtained from these unique sequences of play (i.e., long and immediate next rallies) will assist coaches when modelling and simulating players` performances (i.e., physiologically and cognitively) during athlete preparation/competition.